A chaotic secure communication scheme based on synchronization of double-layered and multiple complex networks - Zhou, Lili; Tan, Fei (Nonlinear dynamics, 2019)
In this paper, we mainly propose a chaotic secure communication scheme which is based on the synchronization of double-layered and multiple complex dynamical networks. Compared with the previous chaotic secure communication schemes, in which only two chaotic systems or just a single-layer network composed of multiple chaotic systems is used, the introduction of a double-layered and multiple complex networks model composed of many encryption/encryption units can not only reflect the complex characteristics of different nodes, but also can improve the complexity and security of information encryption. By using a clustering method, nodes with the same characteristics belong to the same subnet, while the nodes with different characteristics belong to different ones. The subnets in the transmitter and receiver are one-to-one correspondence and form a pair of matching subnets, but the node size of each subnet can be inconsistent. Each subnet is only responsible for encrypting a certain part of information, and thus, the synchronization between each pair of matching subnets plays a crucial role on the correct recovery of information. Multiple encryption/decryption units operating in parallel way can speed up the encryption of information, and the key space can grow with the number of nodes in the transmitter. The proposed scheme utilizes the chaotic signals generated by many chaotic systems as the key sequences and adopts the one-time-one-cipher encryption method. Moreover, this scheme is not subject to the constraint that the amplitude of the encrypted signal should be much smaller than that of the chaotic signal, and it is particularly suitable for the big data encryption. Both theoretical analysis and numerical simulation demonstrate the feasibility and effectiveness of the proposed scheme.